Governance in Lebanese Banks: An Exploratory Research Before theCOVID-19 Era (Asian Business Research, 2021)
Banks locally and abroad have been subject to several financial crises which led top managers to look critically attheir current practices in managing the financial resources in order to avoid losses and to prevent giving a negativeimage to the community of their customers. Parallel to the aforementioned events, banks have been observing anevolution of the banking investment activities in addition to the transformation of the financial market into an openmarket system.The different events characterized by higher risks and higher demands for financial services have incited banks toexplore and emphasize the importance of governance principles. In this study, the researchers will expose theimportance of governance and its main principles in the banking systems. The study will also address theaforementioned pertinent to its implementation according to the activities of Basel Committee on bankingsupervision. The aim of the study is to assess via a quantitative approach the actual governance practices within aconvenient sample of Lebanese banks. The outcomes show that the selected banks abide by the principles ofCorporate Governance required byBasel as well as by the Central Bank of Lebanon. Results also address the effectof sound governance on the performance of the Banks in question. Findings will serve to issue recommendationsabout best practices and to encourage the adoption of sound decisions to adopt Corporate Governance principles.